2011
DOI: 10.1001/archophthalmol.2011.60
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ocular Response Analyzer Parameters in Chinese Subjects With Primary Angle-Closure and Primary Open-Angle Glaucoma

Abstract: Objectives: To evaluate corneal hysteresis (CH) and intraocular pressure (IOP) measured by the Ocular Response Analyzer in Chinese subjects with primary angleclosure glaucoma (PACG), assess their relationship with Goldmann applanation tonometry (GAT) measurements, and compare this with subjects with primary openangle glaucoma (POAG) and normal controls. Methods: In this prospective observational study, consecutive subjects with PACG and POAG without prior intraocular surgery were enrolled from glaucoma clinics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…1,23 Conversely, it has been suggested that low CH might be expected to increase the risk for developing glaucomatous optic neuropathy, possibly due to reduced capacity of the eyewall to dampen IOP spikes 23,24 and/or reduced ability of optic nerve structures to suitably respond to IOP fluctuations. 1,25,26 This premise is supported by several studies, which indicate that eyes with POAG exhibit lower CH compared with normal eyes [1][2][3][12][13][14][15][16] and eyes with OH. 1,12 In addition, lower CH has been linked to both glaucoma progression 17,18 and severity.…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…1,23 Conversely, it has been suggested that low CH might be expected to increase the risk for developing glaucomatous optic neuropathy, possibly due to reduced capacity of the eyewall to dampen IOP spikes 23,24 and/or reduced ability of optic nerve structures to suitably respond to IOP fluctuations. 1,25,26 This premise is supported by several studies, which indicate that eyes with POAG exhibit lower CH compared with normal eyes [1][2][3][12][13][14][15][16] and eyes with OH. 1,12 In addition, lower CH has been linked to both glaucoma progression 17,18 and severity.…”
Section: Introductionmentioning
confidence: 65%
“…Recent research has provided evidence that corneal biomechanical properties may have a meaningful influence not only on intraocular pressure (IOP) measurements [1][2][3][4][5][6][7][8][9][10][11] but also on the ocular effects of IOP. [1][2][3][12][13][14][15][16][17][18][19][20][21][22] Central corneal thickness (CCT) has received the most attention in this regard, spurred by findings from the Ocular Hypertension Treatment Study (OHTS) in which CCT was the strongest independent predictor of conversion from ocular hypertension (OH) to primary open-angle glaucoma (POAG).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations